2020
DOI: 10.1177/0972150920920778
|View full text |Cite
|
Sign up to set email alerts
|

Home Country Innovation Performance: Moderating the Local Knowledge and Inward Foreign Direct Investment

Abstract: The inward foreign direct investment (FDI) has been emphasized in the literature, and although the benefits related to innovation are known, there is not much information about their effects on emerging economies. This study investigates how local domestic factors such as research and development (R&D), exports and foreign technology acquisition moderate with inward FDI to improve the innovation performance. The empirical findings from a generalized method of moments (GMM) estimator suggest, at short term,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
4
0
2
Order By: Relevance
“…This is important, once there is a large number of Brazilian firms working in foreign countries (Viglioni & Calegario, 2020). Thus, we suggest that large size firms are more capable to handle different environments.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…This is important, once there is a large number of Brazilian firms working in foreign countries (Viglioni & Calegario, 2020). Thus, we suggest that large size firms are more capable to handle different environments.…”
Section: Resultsmentioning
confidence: 82%
“…Nevertheless, the returns on R&D is kind lower. Additionally, the result goes in a different direction of Viglioni and Calegario (2020). Using industry-level data, the authors found that R&D does not show significance in short-term.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The overall crowd-in effect can be explained in the literature. Foreign direct investment is known to promote knowledge, technology transfer, exports expansion, product and process innovation ( Djulius, 2017 ; Jawaid et al, 2016 ; Jin et al, 2019 ; Mohanty & Sethi, 2019 ; Schneider & Wacker, 2020 ; Viglioni & Calegario, 2020 ). Whilst employees could share knowledge on the job, labour mobility within the food manufacturing sector (from MNEs to domestic firms), would also lead to knowledge diffusion.…”
Section: Discussion Of Estimationsmentioning
confidence: 99%
“…Entretanto, entender os efeitos das políticas industriais sobre o processo de internacionalização brasileira ainda é um ponto a ser discutido. Essa investigação é relevante, uma vez que durante os anos de implementação das políticas industriais, como a PITCE, a PDP e o PBM, as exportações tiveram efeito positivo na inovação das empresas brasileiras (Viglioni & Calegario, 2020). De maneira similar, as saídas de IDE do país têm sido de suma relevância para o fortalecimento da economia nacional (Alcântara, Paiva, Bruhn, Carvalho, & Calegario, 2016).…”
Section: Introductionunclassified